“A mini home far away from home.” The Thai temple and women’s sense of safety in Finland - Härkönen, Mitra (Frontiers in Psychology, 2024)
This article explores the significance of the Thai Buddhist temple for Thai women's sense of safety in Finland. Despite the growing popularity of Buddhism in the country, research literature and media have largely ignored the religiosity of Thai women, focusing instead on negative stereotypes. The article highlights the importance of Buddhism and the temple in the lives of Thai women who have migrated to European countries and challenges biased portrayals of Thai women in previous research. Based on ethnographic research and life story interviews, the article argues that the temple plays a crucial role in promoting a sense of safety among Thai women by providing a sense of home, belonging, and meaning. The temple's material and symbolic characteristics, in addition to its communality and relationality, work together to connect individuals with the temple's religious significance, contributing to the women's sense of security.Finland, with three established temples and thousands of practitioners. This is mainly due to Thai women living in the country. (Härkönen, 2023b.) Even though Thai women are the primary supporters and promoters of Thai Buddhism in Finland, both research literature and popular media have mostly kept silent about the religiosity of Thai women living in European countries. Instead, the dominant discourse on them has been problemoriented and has concentrated on the stereotypes of Thai women as sex workers or women as submissive victims of Western husbands or human trafficking. (